ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPUASAN KERJA PADA KARYAWAN OPERASIONAL PT. X SEMARANG - Galih Pamungkas; Ekawati Ekawati; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
PT X Semarang is land transportation service company. The observation result of preliminary study showed that there are problems about absent and late work which indicate of unsatisfied at work. The purpose of this research is to analyze the correlation between type of job, supervision, salary, promotion opportunities, and colleague with operational employee’s job satisfaction at PT X Semarang. The type of this research is analytic research that use cross-sectional study which is form of observational research design. Population and sample of this research are 40 operational employees of PT X Semarang. The research instruments are Minnesota Satisfaction Questionare (to measuring job satisfaction) and Job Descriptive Index (to measuring type of job, supervision, salary, promotion opportunities, and colleague). The result of this research is there is correlation between type of job (sig 0,010), supervision (sig 0,027), salary (0,028), and colleague (sig 0,026) with job satisfaction. Meanwhile, there is no correlation between promotion opportunities (sig 0,366) with job satisfaction. There is a 52,5% of operational employee that feel satisfied with their job. To keep and improve operational employee’s job satisfaction, we suggest company to make an activity that contain about teamwork and company should be transparent about company regulation to its employee especially about promotion policy, so that employee can be motivated to improve their performance and competitiveness with their colleagues.